Attitude of Medical Students About Their Role and Social Accountability in the COVID-19 Pandemic - Hong, Jihoon; Jung, Ikjae; Park, Mingeol; Kim, Kyumin; Yeo, Sungook; Lee, Joohee; Suh, Sooyeon; Hong, Youjin; Park, Jangho; Chung, Seockhoon (Frontiers in Psychiatry, 2021)
Introduction This study aimed to explore the attitude of medical students toward their roles and social accountability in this pandemic era. An online survey asked questions covering the topics of 1) the role of medical students in the pandemic era; 2) Medical education in the ‘new normal,’ and 3) the impact of COVID-19 on medical students. Materials and Methods The online survey was distributed to medical students, graduates, and professors in a single South Korean medical school. Anxiety symptom rating scales, including the Stress and Anxiety to Viral Epidemic - 6 (SAVE-6) scale and the Generalized Anxiety Disorder - 7 (GAD-7) scale, were also applied to measure participant anxiety level. Results 213 medical students, 180 graduates, and 181 professors participated in this online survey. Medical students indicated their willingness to join the healthcare response to the COVID-19 pandemic if requested; however, graduates and professors recommended that medical students continue their medical school curriculum. In the new normal era, adequate knowledge of COVID-19 infection and spread must be considered for the continuation of clinical clerkships during the pandemic. Overall, medical students who indicated anxiety about treating possible or confirmed cases rated higher on the SAVE-6 scale. Finally, medical students who reported that COVID-19 had an influence on their studies and daily life rated higher on the GAD-7 scale. Conclusion Social accountability is an important issue for medical students in the pandemic era. At the same time, cultivating professionalism is also important for the readiness for the future healthcare responses.